2021
DOI: 10.1096/fj.202001907r
|View full text |Cite
|
Sign up to set email alerts
|

Impairment of the Hif‐1α regulatory pathway in Foxn1‐deficient (Foxn1 −/− ) mice affects the skin wound healing process

Abstract: Skin, the largest organ of the body, serves as a protective barrier against infections, heat loss, dehydration, and mechanical insults and can sense external (temperature, touch) and internal (neurons, hormones) signals. 1,2 Interruption of skin integrity by injury or surgical intervention can lead to severe damage and abnormal homeostasis. 3 The integrity of the wounded skin is restored through a reparative healing process, which results in scar formation. Although scarring

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
10
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(18 citation statements)
references
References 76 publications
2
10
0
6
Order By: Relevance
“…The similar pattern detected in the reduction levels of MIP-1γ and CD68 mRNA expression, particularly at post-wounding day 3, can indicate the role of the Foxn1/Hif-1α transgenes in the resolution of the inflammatory phase of the healing. The data are in agreement with our previous study that showed the extensive accumulation of CD68-positive cells and higher levels of monocyte chemoattractant protein 1 (MCP-1) in the wounded skin of Foxn1 −/− mice [ 39 ]. Whether Foxn1/Hif-1α, through macrophages content regulation, can contribute to skin wound healing, remains an important issue for future research.…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…The similar pattern detected in the reduction levels of MIP-1γ and CD68 mRNA expression, particularly at post-wounding day 3, can indicate the role of the Foxn1/Hif-1α transgenes in the resolution of the inflammatory phase of the healing. The data are in agreement with our previous study that showed the extensive accumulation of CD68-positive cells and higher levels of monocyte chemoattractant protein 1 (MCP-1) in the wounded skin of Foxn1 −/− mice [ 39 ]. Whether Foxn1/Hif-1α, through macrophages content regulation, can contribute to skin wound healing, remains an important issue for future research.…”
Section: Discussionsupporting
confidence: 93%
“…The process of re-epithelialization was completed on day 6 for LV-empty/control- and LV-Foxn1+LV-Hif-1α-treated mice (100%; Figure 3 ). Our previous study showed 94% of re-epithelialization on post-wounding day 3, and completion of the process on day 5 during skin wound healing of Foxn1 −/− mice [ 39 ]. Observed discrepancies in the re-epithelialization pace between previous and present experiments are most likely caused by LVs injection, per se.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations